Suitability of floating net cage system of lobster cultivation site (Panulirus spp.) through Geographic Information System approach in Samaturu Sub-district, Kolaka District, Indonesia - SYAHRIR SYAHRIR; ARIF PRASETYA; LA ODE ABDUL FAJAR HASIDU; RAMLAH SALEH; ANDI DYNA RIANA; NUR ASIA UMAR; MUHAMMAD YUSUF (Society for Indonesian Biodiversity, 2024)
Abstract. Syahrir, Prasetya A, Hasidu LOAF, Saleh R, Riana AD, Umar NA, Yusuf M. 2024. Suitability of floating net cage system of lobster cultivation site (Panulirus spp.) through Geographic Information System approach in Samaturu Sub-district, Kolaka District, Indonesia. Biodiversitas 25: 4105-4116. The natural habitat of lobsters is in coral reefs of coastal waters from shallow to 100 meters below sea level. In Indonesia, coral reef areas that become the habitat of lobsters are around 67,000 km², including those in the waters of Samaturu Sub-district, Kolaka District, Southeast Sulawesi. The present study uses a floating net cage system to identify and map suitable lobster (Panulirus spp.) cultivation areas. The study was conducted from June to July 2023 in the coastal waters of Samaturu Sub-district, Kolaka District. Data were collected in 14 spots of coastal waters by using various oceanographic parameters (protection, depth, current, brightness, temperature, dissolved oxygen, and salinity). The measurement results of the parameters were analyzed using the spatial analysis method, ArcGIS 10 program. The analysis involved interpolation and spatial classification, which overlaid all oceanographic parameters to obtain the scores through a suitability matrix. Thus, it can show the spatial maps for lobster cultivation areas suitability. The study concluded that the environmental parameter values are: (i) The temperature of the sea surface was 28-30°C; (ii) The salinity level was 31-35 ppt; (iii) The brightness was 5-14 meters; (iv) The dissolved oxygen level was 5-7 mg/L; (v) The current speed was around 0.31-0.41 m/s; (vi) The water depth was 4-26 meters. It means that the measurement results are suitable for lobster cultivation in Samaturu waters; the total area of water suitable for lobster cultivation area with a floating net cage system (KJA) is obtained 6,179 (74.22%), including the highly suitable area is 2,290 ha (27.51%), categorized areas that suitable is 2,363 ha (28.38%), and categorized areas that moderately suitable is 1,526 ha (18.33%). Moreover, there are conditionally suitable areas of 1,648 ha (19.80%) and an unsuitable area of 498 ha (5,98%). Thus, the prospect of developing lobster cultivation in Samaturu waters is potential.